Pride & prejudice - Wright, Joe, 1972-; Bevan, Tim; Fellner, Eric; Webster, Paul; Moggach, Deborah; Hayward, Debra; Chasin, Liza; Osin, Roman, 1960-; Knightley, Keira, 1985-; Macfadyen, Matthew, 1974-; Blethyn, Brenda, 1946-; Sutherland, Donald, 1935-; et al. (Universal City, CA : Universal Studios Home Entertainment, 2006)
Mr. Bennet is an English gentleman living in Hartfordshire with his overbearing wife and 5 daughters. There is the beautiful Jane, the clever Elizabeth, the bookish Mary, the immature Kitty and the wild Lydia. Unfortunately, if Mr. Bennet dies their house will be inherited by a distant cousin whom they have never met. The family's future happiness and security is dependent on the daughters making good marriages. Life is uneventful until the arrival in the neighbourhood of the rich gentleman Mr. Bingley, who rents a large house so he can spend the summer in the country. Mr Bingley brings with him his sister and the dashing, rich, but proud Mr. Darcy. Love soon buds for one of the Bennet sisters, while another sister may have jumped to a hasty prejudgment. For the Bennet sisters many trials and tribulations stand between them and their happiness
Special features: Optional feature audio commentary with director, Joe Wright ; A Bennet family portrait (ca. 6 min.) ; Jane Austen, ahead of her time (ca. 8 min.) ; Behind the scenes at the ball (ca. 6 min.) ; Pride & prejudice: an HBO first look (ca. 13 min.)
Special features include: optional feature audio commentary with director, Joe Wright; A Bennet family portrait (ca. 6 min.); Jane Austen, ahead of her time (ca. 8 min.); behind the scenes at the ball (ca. 6 min.); Pride & prejudice: an HBO first look (ca. 13 min.)
Originally released as a motion picture in 2005
Based on the novel by Jane Austen
Region 1, NTSC, anamorphic widescreen 2.35:1; Dolby Digital 5.1 surround
Director of photography, Roman Osin ; editor, Paul Tothill ; costume designer, Jacqueline Durran ; music by Dario Marianelli ; music supervisor, Nick Angel ; art direction by Nick Gottschalk, Mark Swain ; executive producers, Debra Hayward, Liza Chasin
Keira Knightley, Matthew Macfadyen, Brenda Blethyn, Donald Sutherland, Tom Hollander, Rosamund Pike, Jena Malone, Judi Dench, Kelly Reilly, Claudie Blakley, Peter Wight, Penelope Wilton, Simon Woods, Rupert Friend, Carey Mulligan, Talulah Riley
Keywords: Austen, Jane, -- 1775-1817 -- Film adaptations; Bennet, Elizabeth (Fictitious character) -- Drama; Darcy, Fitzwilliam (Fictitious character) -- Drama; Social classes -- England -- 19th century -- Drama; Young women -- England -- 19th century -- Drama; Women -- England -- Social conditions -- 19th century -- Drama; Courtship -- England -- 19th century -- Drama; Sisters -- Drama; Man-woman relationships -- Drama; England -- 19th century -- Drama; England -- Social conditions -- 19th century -- Drama; England -- Social life and customs -- 19th century -- Fiction; Feature films; Fiction films; Video recordings for the hearing impaired; Romance films; Melodrama -- Feature; Romance -- Feature